Implementasi Augmented Reality Berbasis Android sebagai Media Pembelajaran Matematika Dimensi Tiga - Mardian, Zurni; Defit, Sarjon; Sumijan, Sumijan (Jambura Journal of Informatics, 2023)
Technology has an important role in education, namely, facilitating teacher-student interaction in teaching and learning activities. This is realized by applying technology to learning media. The limitation of space building props in learning high school mathematics on the topic of the Third Dimension requires teacher innovation to develop interactive learning media that can be used at any time. The use of Augmented Reality (AR)-based interactive media with Marker-based Tracking techniques is designed to help students visualize 3D objects well. 3D objects were created using the 3Ds Max software. This research produced a product in the form of an AR Distance in Space application that runs on Android. An AR camera is used to detect markers and display cubes, pyramids, and beam objects. The black-box test results show that the application is as planned and can run normally. This means that the AR Distance in Space applications is categorized as Very Good or receives a positive response from users. This application can be used as an interactive learning media that can facilitate students' understanding of the topic of the Third Dimension and increase student motivation in learning mathematics. Teknologi memiliki peranan penting dalam pendidikan, yaitu memfasilitasi interaksi guru dan murid dalam kegiatan belajar mengajar. Ini diwujudkan dengan menerapkan teknologi dalam media pembelajaran. Keterbatasan alat peraga bangun ruang dalam pembelajaran Matematika SMA topik Dimensi Tiga memerlukan inovasi guru untuk mengembangkan sebuah media pembelajaran interaktif yang dapat digunakan di setiap waktu. Penggunaan media interaktif berbasis Augmented Reality (AR) dengan teknik Marker-based Tracking dirancang untuk membantu siswa memvisualisasikan objek 3D dengan baik. Objek 3D dibuat dengan software 3Ds Max. Pembuatan marker menggunakan Vuforia SDK dan pada Unity dilakukan pengaturan antarmuka dari aplikasi untuk diterapkan pada Android. Penelitian ini menghasilkan produk berupa aplikasi AR Jarak dalam Ruang yang berjalan pada Android. Penggunaan kamera AR digunakan untuk mendeteksi marker dan menampilkan objek kubus, limas, dan balok. Hasil pengujian Black-box menunjukkan bahwa aplikasi telah sesuai yang direncanakan dan dapat berjalan normal. Ini berarti aplikasi AR Jarak dalam Ruang terkategori Sangat Baik atau mendapat respon positif dari pengguna. Aplikasi ini dapat digunakan sebagai media pembelajaran interaktif yang dapat memudahkan siswa dalam memahami topik Dimensi Tiga dan untuk meningkatkan motivasi siswa dalam pembelajaran Matematika.